PENGGUNAAN KITOSAN UNTUK MEMPERPANJANG UMUR SIMPAN BUAH DUKU (Lansium Domesticum Corr) - Hesti Nur'aini; Siska Apriyani (UNIVED Press, Universitas Dehasen Bengkulu, 2015)
Lanzones is a highly perishable fruit because the fruit skin will turn brown within 4 or 5 days after harvest so that the necessary methods of proper post-harvest handling. One alternative that can be used to extend the shelf life lanzones cost is relatively light coating lanzones with chitosan. Chitosan coatings have the ability to delay or slow down the process of extending the maturity and post-harvest storage. Research has been conducted in order to study the effect of chitosan on shelf life, physical and chemical properties of lanzones. The study was conducted in three stages namely stage dilution of chitosan in acetic acid, fruit coating stage lanzones with chitosan solution and analysis phase . The study design used was a completely randomized design, with 2 treatment that chitosan treatment concentration ( 0.5 %, 1.5 % and 2.5 % ) and treatment of immersion time (30 and 60 minutes). The next stage is the lanzones fruit storage at room temperature and shelf life prediction analysis with conventional methods, the analysis of physical ( texture and fruit weight) and chemical analysis (water content and the level of sweetness). The results showed that the use of chitosan coating to prolong the shelf life of lanzones up to 6 days, with the best treatment using 1.5 % chitosan and immersion time of 30 seconds. The higher concentration of chitosan is given, change the texture softening and decreased fruit weight more slowly , with the value of the texture and weight of fruit on the 6th day in a row from 225.83 to 234.59 g / mm and 19.70 to 23.47 g per fruit. Based on the chemical properties of the water content and total dissolved solids , it is known that chitosan coating could inhibit the decrease in water content and total dissolved solids. The immersion time of 30 and 60 seconds is not a real effect. Observations on the 6th day of storage for water content , ranging between 84.44 -87.71 % , while the total dissolved solids ranged from 17.22 to 20.12 % Brix.Keyword : duku, chitosan, shelf life